Methodology for Informed Design of Sustainable Tourism Accommodation in Chile's 9th Region the Gateway to Patagonia. (November 2015) - Whitman, Christopher J.; Armijo, Gabriela; Schiappacasse, L. Nicolas
Abstract: Lying between Chile's agricultural Central Valley and the wilds of Patagonia, the micro region of Araucanía Andina, is seeing a rise in both national and international tourism. With its snow-capped volcanoes, national parks, native forests and indigenous Mapuche culture, the region offers a wide range of activities to the Special Interest Tourist. The development of winter sports facilities and the growth in Northern Hemisphere visitors during the austral winter is extending the season, in what was previously predominantly a destination for Chilean summer holidaymakers. The tourism infrastructure must therefore respond to provide comfortable, energy efficient, sustainable accommodation during both the cold wet winters and short hot summers, meeting the expectations of an ever more demanding international market. The government funded research project "Sustainable Construction System and Energy Efficiency for Special Interest Tourist Infrastructure in the Araucanía Andina, " FONDEF Regional D10R1003, aims to provide the knowledge needed by the local tourist industry to achieve this goal. This paper presents the methodology and outcomes of the project, including the study of local vernacular architecture, post occupation evaluation of existing infrastructure, bioclimatic analysis, environmental and technical assessment of insulation and construction materials, digital simulation of proposals and the construction of physical test cells. The resulting proposal is a system of timber-framed walls, insulated with sheep's wool, finished externally with a ventilated façade. It is hoped that this prefabricated system, in conjunction with best practice guidelines for construction and management, should enable a sustainable future for the region's tourism. At the same time, the methodology provides a replicable template that has already been applied in other regions of the country.